19 - CURRICULAR REFORM IN SLOVAK PRIMARY SCHOOLS AND THE PLACE OF THE MOTOR PERFORMANCE TESTING OF PUPILS IN 1ST AND 3RD GRADE IN IT (Fiep Bulletin - online, 2023)
Started in 2020, a new curriculum reform was launched in Slovakia, which in the first phase is focused on primary and lower secondary education at primary school (Antala 2021; Masaryková 2021). In our article, we want to indicate the direction in which the planned changes should go and how they will also affect the educational field of Health and movement and the school subject of physical and sports education (Pupala and Fridrichová 2022). New curricular reform in regional education will bring these news: changing the structure of education at primary school, creation of a new State Educational Program (SEP) and relevant follow-up documents, placing more emphasis on educational areas than on the subjects themselves, transforming cross-cutting topics into educational areas and subjects, transformation of the Central Subject Committees of the National Institute for Education into a new structure, creation of Regional centres of curricular management and support, free textbook market, new position of Educational area Health and movement and school subject Physical and sport education in new curriculum, motor performance testing of pupils in 1st and 3rd classes as compulsory part of school curriculum.